INTERVENSI AUSTRALIATERHADAP FIJI PASCA KUDETA MILITER - Dany Rukma; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study discusses the Australian intervention against the coup in Fiji, in thisdiscussion mentioned that the Australian state with the fear of a military coup thatoccurred in Fiji negative impact on Australia. Where the export of Australia have ahigh value in Fiji. Australia wants to make the region south pacific is a country thatis harmonious, and prosperous. Australia is a country that is becoming a majorsupplier of goods to the countries that are south pacific region, and it is this that ledto the Australian intervention against Fiji in 2006 to date.Key Words: Australia, south pacific, intervention, military coup